Predicação com o verbo ficar: uso e descrição à luz da linguística funcional - Gomes, Jakeline Simões (2024)
The present work focuses on the predicative clauses with the verb ficar, as in fiquei chocado com as mais de 700 visualizações, fiquei um nojo nesse vestido and fiquei de cara. The main objective is to analyze the phenomenon of predication with this verb in data of use of contemporary Portuguese, as well as to describe the syntactic-semantic and discursivepragmatic characteristics of these clauses. To this end, the research is based on the theoreticalmethodological assumptions of Functional Linguistics, in the North American line and is anchored in the theoretical discussions arising from Bybee (2016), Chafe (1970), Furtado da Cunha, Costa and Cezario (2015), Givón (1991, 1995, 2001), Hopper and Thompson (1980), among others. Methodologically, this is a synchronic research, of a descriptive-explanatory nature, guided by a qualitative approach, with quantitative support, guided by deductiveinductive reasoning (Gerhardt; Souza, 2009). The empirical data make up a corpus consisting of posts linked to various profiles of Rede X, from which 468 samples were investigated between the years 2020, 2021 and 2022. The results indicate that we are facing sentences that, for the most part, present a structure composed of an anaphoric subject of an experiential semantic nature, followed by the verb ficar in the past tense and with an argument in the function of a predicate signaling a continuum that involves everything from adjectives to idiomatic chunks. In addition, the predicative clauses with the verb ficar contemplate both states and changes of states, emphasizing, mainly, changes in more transitory aspects to the detriment of permanent ones, in addition to changes that are more psychological than sensory or physical. In pragmatic terms, the predicative clause tends to occur after the exposure of the event that motivated the expressed state. These clauses also present a tendency to (inter)subjectivity.